Metode Survei Kayu Rakyat Berdasarkan Karakteristik Sosial Ekonomi dan Biofisik Kawasan: Studi Kasus di Kabupaten Bogor (Survey Method for Timber Stand of Private Forest based on Socio-economics and Biophysical Characteristics: a case study in Bogor Dis - Tien Lastini; Endang Suhendang; I Nengah Surati Jaya (Institut Pertanian Bogor (IPB University), 2006)
The objective of this research is to determine the appropriate survey method for timber stand of private forest, based on its important characteristics. There were three methods used in this research, namely, method according to basic data i.e social-economics and biophysic data; method based on image, approached by vegetation transformacy using NDVI; and method based on integration of basic data and image. The result showed that basic data method is the best method for stratification of the village (desa), as a primary sampling unit of the private forest population (district). The second ones is basic data and image-integration method and last ones is image method.Keywords : basic data, coefficient of variation, image, NDVI, private forest, survey method, timber.